JEJAK HISTORIS DAN PERANAN SUNGAI DI KOTA SEMARANG PADA AWAL ABAD 20 - Utama, Nanda Julian; Lusianto, Junaidi Fery (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2019)
This paper will discuss about one part in the history of Semarang City, which is discussing the river from the historical side in the early 20th century. The main problem in this study is how the river and its function in the city of Semarang in the early 20th century. Semarang has always been famous as a large port city on the north coast of Java. Its greatness makes this city have many interesting things to discuss. One of them is the problem regarding the development of this city itself. Since being controlled by Europeans since the 18th century, Semarang has been transformed into a city whose architecture is very similar to European architecture, especially the Netherlands. One interesting part of the city is about the state of the river in Semarang. Similar to some cities in the Netherlands that have many rivers (both natural and artificial), which have many functions, one example is as a flood barrier. In Semarang the function of rivers and canals is also same because the position of this city which is on the coast of the sea. However, whether the function of rivers and canals is only limited to flood control? although not as large as rivers in Sumatra and Kalimantan, the position of rivers in Semarang was also quite important especially in the early 20th century. This paper highlights other functions of rivers in Semarang that have not been revealed in the framework of historical research. The research method used is the historical method, besides this paper also uses primary sources and other relevant sources to answer the problems raised. Keywords: River, ?Kali?, Canal, Port, Semarang, Dutch Colonial.